Exports and Profitability: First Evidence for German Manufacturing Firms - Helmut Fryges; Joachim Wagner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Using unique recently released nationally representative high-quality longitudinal data at the enterprise level for Germany, this paper presents the first comprehensive evidence on the relationship between exports and profitability. It documents that the positive profitability differential of exporters compared to non-exporters is statistically significant, though rather small, when observed firm characteristics and unobserved firm specific effects are controlled for. In contrast to nearly all empirical studies on the relationship between productivity and exports we do not find any evidence for selfselection of more profitable firms into export markets. Due to the sampling frame of the data used we cannot test the hypothesis that firms which start exporting perform better in the years after the start than their counterparts which do not start. Instead, we use a newly developed continuous treatment approach and show that exporting improves the profitability almost over the whole range of the export-sales ratio. Only firms that generate 90 percent and more of their total sales abroad do not benefit from exporting in terms of an increased rate of profit. This means, that the usually observed higher productivity of exporters is not completely absorbed by the extra costs of exporting or by higher wages paid by internationally active firms.
Keywords: F14; D21; 330; exports; profitability; micro data; Germany; Exportindustrie; Verarbeitendes Gewerbe; Rentabilität; Schätzung; Deutschland